Synthesis and evaluation of porous composite hydrogels for tissue engineering applications - Li, Chao (Curtin University, 2012)
The purpose of this dissertation was to synthesize and evaluate porous poly(2- hydroxyethyl methacrylate) (PHEMA) and PHEMA composite hydrogels containing various concentrations of titanium dioxide (TiO2) nanoparticles, silicon dioxide (SiO2) nanoparticles, and multi-walled carbon nanotubes (CNTs) for tissue engineering applications. Eighteen PHEMA nanocomposite hydrogels and five control PHEMA hydrogels were prepared in varying concentrations of water (60-90 wt.%) via a free radical polymerization process. Four of these hydrogels were modified further with an OVICOLL®CLEAR collagen, a mixture of type I and type III collagen, for the improvement of cell activities.Gravimetric analysis and X-ray diffraction analysis, as well as scanning electron microscopy (SEM), were used to examine the presence of the nanoadditives contained in the hydrogel polymers. The presence of collagen also was confirmed using a Fourier transform infrared spectroscope, an ultraviolet-visible spectrophotometer and an SEM.All hydrogels appeared opaque and exhibited various porous structures, which then were studied using a SEM. The porous structures were found to be dependent largely on the HEMA:water concentrations in the polymerisation mixtures. There was no significant difference in the porous structure for PHEMA and PHEMA composite hydrogels containing additives. The results from the polymer volume fraction study also indicated the porous structures of the resultant hydrogels.The tensile properties of the hydrogels were examined using a SINTECH200/M material testing workstation. The viscoelastic properties of the hydrogels were investigated using a HAAKE MARS III Modular Advanced Rheometer System. The mechanical properties of the hydrogels, apparently, were affected by the presence of the porous structures. In general, higher tensile and elastic moduli were seen for hydrogels with less porous structures. In contrast, lower tensile and elastic moduli were seen for more porously structured hydrogels. The addition of TiO2 particulates did not show significant influence on tensile and elastic moduli. However, the addition of CNTs increased the viscoelastic moduli of PHEMA hydrogels, which can be attributed to their fibre characteristics. The hydrogels produced in this study have shown a great range of linear viscoelasticity and a quick recovery characteristic, dependent on the macroporous structures and the presence of the TiO2 nanoadditives.The delivery of a model molecule, methylene blue and three biomolecules, including prednisolone 21-hemisuccinate sodium salt, caffeine, and bovine serum albumin were carried out under static and dynamic conditions. Rheological stimulations were used for the dynamic conditions. The delivery of both single and dual molecules was investigated. It was found that increasing the frequency and the shear strain of the stimulations accelerated the relative biomolecule release under dynamic conditions. However, in comparison to the static conditions, the relative delivery of the biomolecules was slowed by the application of rheological stimulations, due to the reabsorption of the biomolecule into the hydrogel matrix under the dynamic conditions. The release profiles of the biomolecules were affected by the concentrations of the biomolecules and their molecular weights, as well as the porous structures of the hydrogels. When dual biomolecules were utilised in the system, the delivery profile of each of the biomolecules was the same as the single biomolecule delivery profile. The relative release also was dependent on the porous structures and the molecular weights.The biomineralisation of the hydrogels was evaluated with a calcification study. The infiltration of the calcium phosphate was found to be more vigorous in a more porously structured hydrogel, and it was significantly enhanced after TiO2 nanoparticles were incorporated. An assay indicated that PHEMA and its nanocomposite hydrogels were tolerated well by the NIH 3T3 fibroblast cells. However, the cell growth on both PHEMA and PHEMA composite hydrogels was relatively slow. The presence of collagen significantly increased numbers of viable cells on modified hydrogels in comparison to that seen on hydrogels containing no collagen molecules. This was true for two other types of cell, including green fluorescent protein-transfected 253 human melanoma cells and human mesenchymal stem cells.In summary, porous PHEMA composite hydrogels make an excellent family of scaffolding materials for soft tissue regeneration. Their porous structures and mechanical properties can be tailor-made, simply by adjusting the chemical composition in the formulae to meet the requirements of specific applications. The bioactivities of the hydrogels also can be improved by tethering natural molecules without altering the porous structure or the mechanical properties. Biomolecules can be preloaded into the hydrogel matrices by a simple diffusion process at room temperature due to the presence of large pores. The preloaded concentrations and the subsequent delivery of these biomolecules can easily be adjusted by changing the concentrations of the stock solutions. This is highly desirable for an ideal tissue scaffold, which not only can provide interconnected pores and dictated mechanical properties, but also is capable of delivering essential signalling biomolecues for the tissue regeneration process. Therefore, these preliminary investigations of PHEMA and PHEMA composite hydrogels have demonstrated their great potential for tissue engineering applications.